Bond strength of two-step etch-and-rinse adhesive systems to the dentin of primary and permanent teeth - Ricci, Hérica Adad [UNESP]; Sanabe, Mariane Emi [UNESP]; De Souza Costa, Carlos Alberto [UNESP]; Hebling, Josimeri [UNESP] (MRE Press, 2010)
Objective: The purpose of this study was to compare the immediate microtensile bond strength (μTBS) of two-step etch-and-rinse adhesive systems to the dentin of primary and permanent teeth. Study Design: Non-carious human teeth (12 primary molars and 12 premolars) were assigned to 3 groups according to the adhesive system. The adhesive systems were applied to flat superficial coronal dentin surfaces etched with phosphoric acid and composite resin blocks were built up. The teeth were sectioned to produce beam-shaped specimens with 0.81 mm2 cross-sectional area subjected to μTBS testing. μTBS data were analyzed statistically by ANOVA and Tukey's test (a= 0.05). Results: The adhesive systems produced statistically similar mean μTBS to each other (p>0.05) and no significant differences (p>0.05) were found when the same material was applied to primary or permanent tooth dentin. The mean μTBS values (MPa) obtained were: Prime & Bond NT: 41.7±14.4 (permanent) and 40.8±13.4 (primary); Single Bond: 42.9±8.6 (permanent) and 41.4±11.9 (primary); Excite DSC: 46.3±11.3 (permanent teeth) and 43.4±12.0 (primary). Conclusion: There was no difference in the immediate μTBS of two-step etch-and-rinse adhesive systems when applied to the dentin of primary and permanent teeth.
Keywords: Deciduous; Dentin; Dentin-Bonding Agents; Dentition; Permanent; Tensile Strength; Tooth